Deployment of Private Cloud and Analysis of data for Business Case - Arora, Paras; Kumar, Raj (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing technology has been emerging and spreading at a great pace due to its service oriented architecture, elasticity, cost-effectiveness, etc. Many organizations are using Infrastructure-as-a-Service (IaaS) public Clouds for data migration away from traditional IT Infrastructure but there are a few fields such as finance, hospitals, military and others that are reluctant to use public Clouds due to perceived security vulnerability. Enterprises in such fields feel more vulnerable to security breaches and feel secure using in-house IT infrastructure. The introduction of private Clouds is a solution for these businesses. This paper focuses on deployment of private Cloud with the help of apache cloud stack, Analysis of data for Building the Business case for Private Cloud. I have proposed a platform and evaluated a service oriented IaaS model of private Cloud which provides a platform to the business suite to sell it as a PaaS service to the customers. Comparative analysis includes cloud services delivery (SaaS, PaaS, IaaS) and deployment models (private, public, and hybrid).